Records of travels in Turkey, Greece, &c., and of a cruise in the Black Sea, with the capitan pasha, in the years 1829, 1830, and 1831, vol. 1 - Slade, Adolphus. (London)
2 c. (xvi, 519 s. ; viii, 513 s.)